10.5k views
4 votes
Solve the following: -7(1 - 8x) = 105

User Mijc
by
5.3k points

2 Answers

4 votes

Answer:

x = 2

Explanation:

Rearrange the values: -7(1 - 8x) = 105 = -7(-8x + 1) = 105

Distribute: -7(-8x + 1) = 105 = 56x -7 = 105

Add 7 to both sides of the equation: 56x -7 = 105 = 56x -7 + 7 = 105 + 7

Simplify: 56x -7 + 7 = 105 + 7 = 56x = 112

Divide both sides of the equation by the same term: 56x = 112 = 56x/56 = 112/56

Simplify: 56x/56 = 112/56 = x = 2

User KeylorSanchez
by
4.4k points
3 votes

Answer:

2

Explanation:

-7 (1-8x) = 105

-7 - (-56x) = 105

-7 +56x = 105

+56x = 105 + 7

56x = 112

56x/56 = 112/56

x = 2

Let me know if you need more help!

User MkMan
by
5.9k points